Impacto da infusão mesentérica de compostos nitrogenados sobre o fluxo visceral de metabólitos em ovinos - Stefanello, Simone (2016)
The aim of the study is measure the impact of the mesenteric infusion of different N compounds: alanine, arginine and ammonium bicarbonate on oxygen uptake by splanchnic tissues relative the ureagenesis and gluconeogenesis. In an attempt to quantify the digestibility diet initially and after visceral metabolism, a trial with four multicatheterized wethers (45±2 kg body weight) was conducted as a 4 × 4 Latin Square feeding Tifton hay (2,5 %) and protein concentrate (0,7%) with 210 minutes daily periods during 4 days. The data obtained in the digestibility trial were complementary to those obtained in metabolism trial. The blood flow through portal- drained viscera (PDV) and total splanchnic tissues (ST) were determined by downstream dilution of 15 g/L p-aminohippurate (PAH) infused continuously (1.5mL/min) into the mesenteric vein. In parallel, wethers were continually infused into the mesenteric vein with aphysiological saline (0.15 MNaCl) solution during 90 minutes followed by the infusion, during more 120 minutes, of either solution: physiological saline (control), 0.25 MNH4HCO3, 0.25 M L-alanine or 0.125 M L-arginine, all of them infused at a rate of 1.5 mL/min to provide 375 μmol N/min. The infusion of nitrogenous compounds and their greater hepatic uptake increased hepatic O2 spent as a result of an increase in ureagenesis, which was not observed for gluconeogenesis. The higher ammonia portal circulation increases urea synthesis and thus the energy cost. O2 expense associated with the urea synthesis is higher than O2 expense related to gluconeogenesis. Increased alanine or arginine uptake by liver did not change the cost of O2. Moreover, it was not possible to compare the amino acids in study, since the infusion of arginine did not change any of the variables examined.